2022
DOI: 10.4103/ams.ams_141_21
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Reality in the Reconstruction of Orbital Floor: An Experimental and Clinical Evaluative Study

Abstract: Introduction: Orbital floor fractures are common within midface fractures. Their management includes restoration of orbital volume and anatomy. However, these procedures could be associated with the mispositioning of implants and inadequate volume restoration. Nowadays medical rapid prototyping, virtual planning (VP), and navigation systems significantly increase the precision of such procedures. Nevertheless, the application of intraoperative navigation could be associated with intraoperative mis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Rahimov et al showed a mean deviation of 0.9 mm, ranging from 0.65 to 1.15 mm [ 20 ]. However, this study was performed using Microsoft HoloLens-printed skulls.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rahimov et al showed a mean deviation of 0.9 mm, ranging from 0.65 to 1.15 mm [ 20 ]. However, this study was performed using Microsoft HoloLens-printed skulls.…”
Section: Resultsmentioning
confidence: 99%
“…However, this study was performed using Microsoft HoloLens-printed skulls. In two cases, the surgeon was not able to concentrate their attention on both holographic and real objects [ 20 ]. Another study [ 19 ] calculated the technical accuracy of a Microsoft HoloLens on printed fractured orbits by calculating fiducial registration errors, target registration errors and guidance errors.…”
Section: Resultsmentioning
confidence: 99%
“…Mixed reality (MR) can address the effects of inadequate visualization of intraoperative 2D images and unintuitive presentation of the affected area and can greatly alleviate the hand-eye incongruity associated with viewing medical images during surgery. Rahimov et al (2022) incorporated virtual planning and MR techniques into orbital reconstruction surgery, using virtual planning to develop a detailed and accurate surgical plan and then MR to make the preoperatively developed surgical plan visible to the surgeon in real time, providing intraoperative navigation for orbital reconstruction. After the actual clinical trial, it was found that the patient's eye mobility improved and diplopia was reduced after the surgical reconstruction.…”
Section: Trauma and Facial Reconstructionmentioning
confidence: 99%